(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research was conducted to obtain a clear description of the use of Uslub Istifham in Surah Al-A’raf so that it can be implied in teaching Balaghah Science at the Arabic Language Study Program, Indonesian Muslim University. The method used in this study is a qualitative descriptive method by analyzing the use of ushlub istifham in Surah Al-A’raf. The method used by researchers in collecting data in this study is the documentation method and the recording method. Uslubul Istifham is a question sentence, and the question sentence in Balaghah science often has another meaning. Based on the data obtained from surah al-a’raf about adawat istifham in surah al-a’raf, from 206 verses in surah al-a’raf there are 49 istifham sentences from 47 verses (12, 22, 28, 32, 37 , 44, 48, 49, 53, 63, 65, 69, 70, 71, 75, 80, 81, 84, 86, 88, 93, 97, 98, 99, 100, 103, 110, 113, 123, 127, 129, 140, 147, 148, 150, 155, 164, 169, 172, 173, 183, 184, 185, 187, 191, 193, 195) and in the form of adawat istifham 47 verses. This discussion can be applied in teaching Balaghah science so that Arabic language students do not receive many difficulties when studying Balaghah science, especially in the discussion of Uslubul Istifham.